Transcriptional regulation and responses in filamentous fungi exposed to lignocellulose - Daly, Paul; van Munster, Jolanda M.; Archer, David B.; Raulo, Roxane (Bentham Science, 2015)
Biofuels derived from lignocellulose are attractive alternative fuels but their production suffers from a costly and inefficient saccharification step that uses fungal enzymes. One route to improve this efficiency is to understand better the transcriptional regulation and responses of filamentous fungi to lignocellulose. Sensing and initial contact of the fungus with lignocellulose is an important aspect. Differences and similarities in the responses of fungi to different lignocellulosic substrates can partly be explained with existing understanding of several key regulators and their mode of action, as will be demonstrated for Trichoderma reesei, Neurospora crassa and Aspergillus spp. The regulation of genes encoding Carbohydrate Active enZymes (CAZymes) is influenced by the presence of carbohydrate monomers and short oligosaccharides, as well as the external stimuli of pH and light. We explore several important aspects of the response to lignocellulose that are not related to genes encoding CAZymes, namely the regulation of transporters, accessory proteins and stress responses. The regulation of gene expression is examined from the perspective of mixed cultures and models are presented for the nature of the transcriptional basis for any beneficial effects of such mixed cultures. Various applications in biofuel technology are based on manipulating transcriptional regulation and learning from fungal responses to lignocelluloses. Here we critically access the application of fungal transcriptional responses to industrial saccharification reactions. As part of this chapter, selected regulatory mechanisms are also explored in more detail.